2015
DOI: 10.3390/jcm4071348
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Nephropathy and CKD—Analysis of Individual Patient Serum Creatinine Trajectories: A Forgotten Diagnostic Methodology for Diabetic CKD Prognostication and Prediction

Abstract: Creatinine is produced in muscle metabolism as the end-product of creatine phosphate and is subsequently excreted principally by way of the kidneys, predominantly by glomerular filtration. Blood creatinine assays constitute the most common clinically relevant measure of renal function. The use of individual patient-level real-time serum creatinine trajectories provides a very attractive and tantalizing methodology in nephrology practice. Topics covered in this review include acute kidney injury (AKI) with its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Furthermore, acceleration or deceleration was observed in a small minority of trajectories. There was no evidence that acute kidney injury or series of it, as suggested by others (6,7), leads to onset of ESRD in a significant proportion of patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, acceleration or deceleration was observed in a small minority of trajectories. There was no evidence that acute kidney injury or series of it, as suggested by others (6,7), leads to onset of ESRD in a significant proportion of patients with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 72%
“…The decline trajectory and underlying mechanisms are not well understood. Theoretically, the decline may be abrupt, as in acute renal failure (6), episodic with plateaus or periods of improvement (7), or inexorably progressive (8). Each pattern points to a different pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…clinical interpretation of patterns in serial eGFR measures remains an important part of case management (46). This study found that the degree of albuminuria was a predictor of all-cause mortality independent of eGFR categories both in the full FDS1 cohort and in the subset in whom trajectories were determined.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, the application of logic and other decision support systems in the electronic health record (EHR) could be leveraged to enhance biochemical surveillance and monitoring paradigms to improve renal outcomes in hospitals (31,32). We have demonstrated that the utility of serum creatinine trajectories in the real-time management of AKI in hospitalized patients cannot be over-emphasized (33). Chaumont et al have suggested that appropriate renal dosing of ACE inhibitors could lead to significantly reduced nephrotoxicity associated with this class of drugs (34).…”
Section: Resultsmentioning
confidence: 99%